Odpowiedzi

2010-01-19T21:07:59+01:00
2x+y=9 |*4
5x-4y=3

8x+4y=36
5x-4y=3
---------
13x=39
x=3

2*3+y=9
6+y=9
y=9-6
y=3



x-2y=3
-2x+y=0 |*2

x-2y=3
-4x+2y=0
----------
-3x=3
x=-1

-1-2y=3
-2y=3+1
-2y=4
y=-2


2010-01-19T21:09:23+01:00
2x+y=9
5x-4y=3

y=9-2x
5x-(4*(9-2x))=3

y=9-2x
5x-(36-8x)=3

y=9-2x
13x=39 |:3

y=9-2x
x=3

y=9-2*3=9-6=3





x-2y=3
-2x+y=0

x=3+2y
-2(3+2y)+y=0

x=3+2y
-6-4y+y=0

x=3+2y
-3y=6 |:-3

x=3+2y
y=-2

x=3-4=-1
Najlepsza Odpowiedź!
2010-01-19T21:11:30+01:00
2x+y=9
5x-4y=3
y=9-2x
5x-4*(9-2x)=3
y=9-2x
5x-36+8x=3
y=9-2x
5x+8x=39
y=9-2x
13x=39
y=9-2x
x=3
y=9-2*3
y=3
x=3

teraz drugie

x-2y=3
-2x+y=0
x=3+2y
-2*(3+2y)+y=0
x=3+2y
-6-4y+y=0
x=3+2y
-3y=6
y=-2
x=3+2*(-2)
y=-2
x=-1
1 5 1